Large Earthquakes Driven by Fluid Overpressure: The Apennines Normal Faulting System Case. Issue 4 (30th March 2020) - Chiarabba, C.; Buttinelli, M.; Cattaneo, M.; De Gori, P.
Abstract: Fluid overpressure is a primary mechanism behind fault interaction and earthquakes triggering. The Apennines section within the young Alpine mobile belt is a key locus to investigate the interplay between fluids and faults. Here, seismicity develops along the extending mountain belt and the key role of fluids has been invoked in past large earthquake sequences. In this study, we use seismological data to get improved images of the Apennines normal faulting system, trying to catch evidences for the involvement of fluids in the preparatory phase of large earthquakes. We observe that extension preferentially reutilizes inherited fragments of faults which were assembled during the Mio‐Pliocene contraction, with steep segments that floor on a regional‐scale gently east dipping plane. We find evidences for wide volumes of overpressured fluids at the base of the seismogenic layer, which are connected to the activation of the recent large earthquakes. The recognition of fluids compartments with overpressuring and diffusion molding seismicity is a key to understand faulting processes and possibly develop forecasts scenarios. Plain Language Summary: We present the first full image of the deep structure of the paradigmatic normal faulting system of the Apennines, obtained by an impressive set of seismological data collected during seismic sequences originated in the past two decades. The synoptic view permits to explore the interaction between earthquakes and fluids within the crust. Such interaction is every day more important because fluid pressure changes in the subsurface (even created by human activities) might trigger large earthquakes even at a distance. The novelty of our results is the imaging of deep fluids at the base of the extensional fault system in the Apennines related to the development of all the large earthquakes that occurred over the two decades. This finding breaks through a persistent problem in earthquake preparation processes and has clear implications for tectonics of extensional systems, inversion tectonics, physics of earthquakes, and aftershock forecasting. Key Points: The complex and diffuse fault segmentation of fault system derives from intense preexisting crustal heterogeneity Large‐magnitude earthquakes along the system are related to broad high Vp/Vs overpressurized volumes at the base of the seismogenic layer Monitoring of this target will help decipher the interaction between deep fluids and seismicity before and during major seismic sequences